Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1365-2591.2008.01434.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of different gutta‐percha techniques when filling experimental internal resorptive cavities

Abstract: Warm gutta techniques filled artificial resorption cavities significantly better than the other gutta-percha techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 14 publications
2
45
0
7
Order By: Relevance
“…Nos estudos de Agarwal et al 7 e Gencoglu et al 15 , podese verificar que, na obturação de canais, em dentes com cavidades criadas artificialmente, os sistemas de obturações termoplastificadas foram significativamente melhores no preenchimento da área de reabsorção, quando comparados com o sistema de condensação lateral a frio. Assim, as técnicas obturadoras selecionadas para este estudo foram a híbrida de Tagger e o uso do sistema ultrassônico.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Nos estudos de Agarwal et al 7 e Gencoglu et al 15 , podese verificar que, na obturação de canais, em dentes com cavidades criadas artificialmente, os sistemas de obturações termoplastificadas foram significativamente melhores no preenchimento da área de reabsorção, quando comparados com o sistema de condensação lateral a frio. Assim, as técnicas obturadoras selecionadas para este estudo foram a híbrida de Tagger e o uso do sistema ultrassônico.…”
Section: Discussionunclassified
“…Foi utilizado um programa de computador Image Tool® a fim de avaliar o preenchimento com material obturador da cavidade reabsorvida por meio do cálculo da porcentagem da área, assim como no estudo de Gencoglu et al 15 , que utilizaram um programa similar, Image Pro® Plus (Media Cybernetics, Inc., Silver Spring, MD, USA), para calcular a porcentagem de obturação.…”
Section: Discussionunclassified
“…16,17 Kök kanal dolgusunun kalitesine yönelik daha önceki birçok çalışmada güta-perka, kanal patı ve boşluklar kesit alma yöntemi ile değerlendirilmiştir. [18][19][20][21] Elde edilen bulgular sonucunda genel olarak sıcak vertikal kompaksiyon yönteminde soğuk lateral kompaksiyon ve açılı tek kon yöntemine göre güta-perka kaplı alanın daha fazla olduğu gözlendi. Ayrıca açılı tek kon yönteminde soğuk lateral kompaksiyon yöntemine kıyasla güta-perka kaplı alanın daha fazla olduğu gözlendi.…”
Section: Bulgularunclassified
“…The thermoplasticity of different types of gutta-percha is affected by their chemical compositions 15,17,18 as well as the thermal changes induced during the manufacturing process and the use of these materials. 17 Although several endodontic techniques have been evaluated with respect to their ability to adequately fill the root canal and its irregularities, 9,11,12 few studies have focused on the thermoplasticity of different brands of guttapercha and Resilon when using thermoplastic techniques. 8,19,20 Resilon (Resilon Research LLC, Madison, USA), a synthetic polymer-based material, has been proposed as an alternative to gutta-percha.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In this regard, several filling techniques employing thermoplastic guttapercha have been evaluated for their effectiveness in filling irregular or lateral root canals. 9,[11][12][13][14] Evaluation of thermoplastic root canal filling techniques showed that assessment of the properties of gutta-percha in response to heat is of paramount importance. 15,16 .…”
Section: Introductionmentioning
confidence: 99%